Integration of Community Pharmacists in Transition of Care (TOC) Services: Current Trends and Pharmacist Perceptions. (February 2019) - Zeleznikar, Elizabeth A.; Kroehl, Miranda E.; Perica, Katharine M.; Thompson, Angela M.; Trinkley, Katy E.
Background: Barriers exist for patients transitioning from one health-care setting to another, or to home, and health-care systems are falling short of meeting patient needs during this time. Community pharmacist incorporation poses a solution to the current communication breakdown and high rates of medication errors during transitions of care (TOC). The purpose of this study was to determine community pharmacists' involvement in and perceptions of TOC services. Methods: Cross-sectional study using electronic surveys nationwide to pharmacists employed by a community pharmacy chain. Results: Of 7236 pharmacists surveyed, 546 (7.5%) responded. Only 33 (6%) pharmacists reported their pharmacy participates in TOC services. Most pharmacists (81.5%) reported receiving discharge medication lists. The most common reported barrier to TOC participation is lack of electronic integration with surrounding hospitals (51.1%). Most pharmacists agreed that (1) it is valuable to receive discharge medication lists (83.3%), (2) receiving discharge medication lists is beneficial for patients' health (89.1%), (3) discharge medication list receipt improves medication safety (88.8%). Conclusions: Most pharmacists reported receiving discharge medication lists and reported discharge medication lists are beneficial, but less than half purposefully used medication lists. To close TOC gaps, health-care providers must collaborate to overcome barriers for successful TOC services.